The environmental unconscious : ecological poetics from Spenser to Milton - Swarbrick, Steven, 1984- (University of Minnesota Press, 2023)
"Introducing concepts from psychoanalysis as keys to understanding the force of early modern ecopoetics, Swarbrick urges literary critics and environmental scholars fluent in the new materialism to rethink notions of entanglement, animacy, and consciousness raising. Ultimately, he offers a provocative challenge to ecocriticism that, under the current regime of fossil capitalism in which everything solid interconnects, a new theory of disconnection is desperately needed"--